Correlation between genetic and geographic structure in Europe - Lao, Oscar; Lu, Timothy T; Nothnagel, Michael; Junge, Olaf; Freitag-Wolf, Sandra; Caliebe, Amke; Balaščáková, Miroslava; Bertranpetit, Jaume; Bindoff, Laurence A; Comas, David; Holmlund, Gunilla; Kouvatsi, Anastasia; et al. (Current biology, 2008)
Understanding the genetic structure of the European population is important, not only from a historical perspective, but also for the appropriate design and interpretation of genetic epidemiological studies. Previous population genetic analyses with autosomal markers in Europe either had a wide geographic but narrow genomic coverage [1, 2], or vice versa [3-6]. We therefore investigated Affymetrix GeneChip 500K genotype data from 2,514 individuals belonging to 23 different subpopulations, widely spread over Europe. Although we found only a low level of genetic differentiation between subpopulations, the existing differences were characterized by a strong continent-wide correlation between geographic and genetic distance. Furthermore, mean heterozygosity was larger, and mean linkage disequilibrium smaller, in southern as compared to northern Europe. Both parameters clearly showed a clinal distribution that provided evidence for a spatial continuity of genetic diversity in Europe. Our comprehensive genetic data are thus compatible with expectations based upon European population history, including the hypotheses of a south-north expansion and/or a larger effective population size in southern than in northern Europe. By including the widely used CEPH from Utah (CEU) samples into our analysis, we could show that these individuals represent northern and western Europeans reasonably well, thereby confirming their assumed regional ancestry.
Keywords: populační genetika; jednonukleotidový polymorfismus; Polymorphism, Single Nucleotide; Genotype; lidé; běloši; Humans; Linkage Disequilibrium; Geography; vazebná nerovnováha; zeměpis; genotyp; Evropa; White People; Europe; Genetics, Population